2013
DOI: 10.1002/asna.201211967
|View full text |Cite
|
Sign up to set email alerts
|

The P1/P2 period ratio for kink oscillations of an asymmetrical coronal loop

Abstract: Here we investigate the effect of asymmetry of coronal loops on the P1/P2 period ratio of kink transverse loop oscillations. The P1/P2 period ratio technique is used for the diagnostics of the longitudinal structuring of coronal loops as its deviation from the canonical value of 2 is related to the density scale-height along coronal loops. The analysis is carried out by calculating the period of the fundamental and first overtone of magnetohydrodynamic (MHD) kink oscillations for loops with different asymmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Theoretically, the ratios of the fundamental kink mode period P (1) kink to the n-th parallel harmonic period, P (1) kink /(nP (n) kink ), have been shown to depend on the wave dispersion, i.e., the effects of finite k z , gravitational stratification, axial and perpendicular density structuring, loop cross-sectional ellipticity and geometry, and the axial magnetic field non-uniformity due to field expansion (e.g., Andries et al 2009b, and references therein). With regards to the density non-uniformity, this also depends upon the loop's temperature, curvature, inclination, etc., that affect the density scale-height and thus the harmonic period ratios (Orza et al 2012;Orza and Ballai 2013). For example, Ruderman et al (2016) showed that the period ratio P (1) kink /(2P (2) kink is lower or greater than unity when the kink speed increases or decreases with height, respectively.…”
Section: Theoretical Modelling Of the Period Ratiomentioning
confidence: 99%
“…Theoretically, the ratios of the fundamental kink mode period P (1) kink to the n-th parallel harmonic period, P (1) kink /(nP (n) kink ), have been shown to depend on the wave dispersion, i.e., the effects of finite k z , gravitational stratification, axial and perpendicular density structuring, loop cross-sectional ellipticity and geometry, and the axial magnetic field non-uniformity due to field expansion (e.g., Andries et al 2009b, and references therein). With regards to the density non-uniformity, this also depends upon the loop's temperature, curvature, inclination, etc., that affect the density scale-height and thus the harmonic period ratios (Orza et al 2012;Orza and Ballai 2013). For example, Ruderman et al (2016) showed that the period ratio P (1) kink /(2P (2) kink is lower or greater than unity when the kink speed increases or decreases with height, respectively.…”
Section: Theoretical Modelling Of the Period Ratiomentioning
confidence: 99%
“…However, since the loop length varies in their model (see page 3 in Orza & Ballai 2013), the difference between the lengths and also the longitudinal density slopes of the two sides of the loop can reach the values much greater than those of our model. For instance, in the model of Orza & Ballai (2013) for α = 0.6, the loops length changes by 21% in comparison with a semi-circular loop, and the length difference between the two sided is 46.7% of the loop length. Accordingly it shows that a large degree of asymmetry is needed in the coronal loops to affect the period ratio by a few percents.…”
Section: Asymmetric Loopmentioning
confidence: 99%
“…(2010) have made investigations in order to interpret the nature of and the mechanisms behind the asymmetric spectra of transition region or coronal medium structures. Orza & Ballai (2013) attributed the asymmetrical nature of a coronal loop to its shape and studied MHD oscillations of asymmetric coronal loops in various degrees of asymmetricity. Their results indicated that, in the presence of longitudinal stratification of mass density, when the temperature is the same inside and outside the loop, the asymmetry can alter the kink wave period ratio P 1 /P 2 by 5−8%.…”
Section: Introductionmentioning
confidence: 99%
“…Ruderman (2003) studied the period of oscillation and resonant damping of coronal loops with elliptic cross-sections. Morton & Erdélyi (2009) demonstrated curvature of the loop axis, with an elliptic shape, has a small effect on the period ratio, while Orza & Ballai (2013) showed coronal loops being asymmetrical also has a small effect on the ratio. Chen et al (2014) studied the effect of steady siphon flows and found that it significantly reduces the P 1 {nP n ratio.…”
Section: Introductionmentioning
confidence: 97%